PHILOSOPHY OF ISLAMIC EDUCATION(STUDY ON THE ROLE OF RELIGIOUS ORGANIZATIONS, ISLAMIC EDUCATIONAL THOUGHT AND EFFORTS TO BUILD ISLAMIC EDUCATION) - Suhari Suhari; Suhana Sarkawi (Adisam Publisher, 2023)
Community organization or abbreviated as mass organization is a term used in Indonesia for mass-based organizations that are formed with certain goals based on mutual agreement. Mass organizations can be formed based on several similarities or goals, for example: religion, education and social. Thus, Islamic mass organizations can be defined as mass-based organizations united by the aim of fighting for the establishment of the Islamic religion in accordance with the Koran and Sunnah and advancing Muslims in various fields; both in the fields of religion, education, social and culture. Organizations are neutralizers in implementing the norms that apply in society. One of them is a religious organization, its aim is to provide understanding to its followers. To carry out the vision and mission of a religious organization, of course it cannot be separated from thoughts, one of which is Islamic education. From the ideas and ideas of these thinkers they will contribute to efforts to build and develop Islamic education.